2016
DOI: 10.1002/2016jc011697
|View full text |Cite
|
Sign up to set email alerts
|

A snapshot of internal waves and hydrodynamic instabilities in the southern Bay of Bengal

Abstract: Measurements conducted in the southern Bay of Bengal (BoB) as a part of the ASIRI‐EBoB Program portray the characteristics of high‐frequency internal waves in the upper pycnocline as well as the velocity structure with episodic events of shear instability. A 20 h time series of CTD, ADCP, and acoustic backscatter profiles down to 150 m as well as temporal CTD measurements in the pycnocline at z = 54 m were taken to the east of Sri Lanka. Internal waves of periods ∼10–40 min were recorded at all depths below a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Nevertheless, lag correlation and composite analyses suggest that propagation of the coastal trapped intraseasonal Kelvin waves is responsible for the intraseasonal SSC anomalies along the south coast of Sumatra and Java. In addition, the intraseasonal SSC anomalies south of the Sunda and Lombok straits are attributed to the active mesoscale eddies in the southeastern tropical Indian Ocean, which is reminiscent the phenomenon that high SSC co-occurred with the Sri Lanka dome [5][6][7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, lag correlation and composite analyses suggest that propagation of the coastal trapped intraseasonal Kelvin waves is responsible for the intraseasonal SSC anomalies along the south coast of Sumatra and Java. In addition, the intraseasonal SSC anomalies south of the Sunda and Lombok straits are attributed to the active mesoscale eddies in the southeastern tropical Indian Ocean, which is reminiscent the phenomenon that high SSC co-occurred with the Sri Lanka dome [5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…2021, 13, x FOR PEER REVIEW 2 of 20 deeper layer and runoff, respectively (Figure 1a). The global SSC is found subject to multiscale variability associated with ocean dynamical processes such as upwelling, mesoscale eddies, and sea ice melting [4][5][6][7]. Previous investigations show no significant trend in global annual median chlorophyll-a from 1998 to 2015 [8].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Phaniharam et al 10 studied IW characteristics along the northwestern BOB using SAR imagery. In addition, using in situ observations in the southern BOB, Lozovatsky et al 11 studied highfrequency internal wave activity, and Wijesekera et al 12 studied their characteristics and dynamics. Later, modeling studies by Jensen et al 13 revealed that the IWs generated off the Andaman and Nicobar…”
Section: Introductionmentioning
confidence: 99%
“…Formation of mesoscale eddies and inertial waves [8,9] in the BoB stir water in the interior of the Bay, leading to a cascade of smaller scale local instabilities. Turbulence so generated produces mixing and vertical exchange of physical properties as well as biogeochemical fluxes, influencing the BoB ecosystem and strong near surface stratification in the region restricts turbulence to a thin surface boundary layer [10].…”
Section: Introductionmentioning
confidence: 99%